Pengaruh Struktur Modal, Likuiditas Dan Profitabilitas Terhadap Kinerja Keuangan (Studi Kasus Pada Perusahaan Food and Beverage Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Annisa Shalmi Jhon; Enny Arita (CV. ITTC INDONESIA, 2024)
The aim of this research is to determine the influence of capital structure, liquidity and profitability on the financial performance of companies in the food and beverage subsector manufacturing sector listed on the Indonesia Stock Exchange for the 2020-2022 period. The variable used to measure capital structure is the debt to equity ratio (DER), the liquidity variable is measured by the current ratio (CR), profitability is measured by return on assets (ROA), and the financial performance variable is measured by return on equity (ROE). The population of this research is food and beverage subsector manufacturing companies listed on the IDX for the 2020-2022 period with a total of 84 companies. Using purposive sampling and random sampling, a sample of 25 companies was taken. The analysis technique used is multiple linear regression analysis and hypothesis testing and classical assumption tests are also carried out which include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests, with an alpha significance level of 5%. The research results show that the capital structure variable (DER) has no influence on ROE. The liquidity variable (CR) has no effect on ROE, while the profitability variable (ROA) has a significant effect on ROE. The variables capital structure (DER), liquidity (CR) and profitability (ROA) simultaneously influence ROE.